CLASSIFICATION OF TRANSFORMATION PROCESSES IN THE BANKING SYSTEM - Hariaha, Lesia (Socio-economic relations in the digital society, 2020)
Modern conditions of development of banking systems in the world are characterized by significant variability, growing globalization and digitalization, increasing risks and uncertainty. In such conditions, the banking system undergoes appropriate transformational changes. The purpose of the article is to clarify the classification of transformation processes in the banking system.The place of the banking system in the economic system of the country and its relationship with the credit and financial systems has been examined in the article. Approaches to the definition of the concept of «banking system» are generalized and its main functions have been systematized depending on the types of interpretation. The essence of transformation processes in the banking system have been investigated. It has been proposed to group the transformation processes in the banking system depending on the types of interpretation and functions of the banking system. The necessity of research of transformation processes both at the level of the central bank and at the level of the bank (banks) has been substantiated. The classification of transformation processes at the level of the central bank and at the level of banks from the standpoint of interpretation of the banking system as a set of institutional units has been specified. At the level of the central bank, the transformation of the central bank itself and the transformation of the functions of the central bank are highlighted; at the level of the bank (banks) the transformation of the banking sector (as a set of banks), the transformation of an individual bank (as a structural unit within the functioning system), the transformation of banking products has been distinguished. The main transformation processes for the last ten years in the banking system of Ukraine both at the level of the National Bank of Ukraine and at the level of the bank (banks) have been described.Thus, the study of transformation processes in the banking system allows us to state the following: 1) transformation processes of the banking system should be considered as an internal component of the banking system within the transformation function and as a multidimensional and multilevel transition of the banking system from one qualitative state to another; 2) for a comprehensive analysis, transformation processes should be studied at the level of the central bank and at the level of banks; 3) current trends in the economy and society, in particular the pandemic, make significant adjustments to the transformation processes of the banking system, in particular in terms of accelerating the transition to online mode and the need to constantly adapt and adapt to new conditions, while performing all functions of the banking system. its stability.
Keywords: bank; central bank; banking system; functions of the banking system; transformation processes; classification of transformation processes in the banking system